A Case of Old Myocardial Infarction with ST Elevation after Conversion to Sinus Rhythm by Intravenous Disopyramide Phosphate in Transient Atrial Fibrillation - HATA Nritake; KUNIMI Toshihiro; TAKANO Masamichi (Japanese Journal of National Medical Services, 1999)
The prevention of embolism is important in cases with defibrillation of atrial fibrillation. In chronic atrial fibrillation, there is some protocol for preventing the occurrence of embolisms, but no precise protocol in transient atrial fibrillation. A woman with transient atrial fibrillation was admitted to our hospital. She had the history of acute myocardial infarction, diabetes mellitus, hypertension and hyperlipidemia. Disopyramide phosphate (45 mg) was administrated intravenously and the rhythm was converted to sinus rhythm. After defibrillation, ST elevation on electrocardiography and the increase of the enzyme conserning with myocardium. In this patient, disopyramide phosphate was administrated later, but no electrocardiographic change were revealed. Coronary angiography revealed three vessel disease but not spastic. So, coronary embolism was strongly suspected. Some reports were seen about the electrocardiographic changes following the use of anti-arrhythmic agents, but the mechanism of those changes were due to conduction disturbance. Our case seems to be rare case with coronary embolism after pharmacological defibrillation of transient atrial fibrillation. 心房細動の除細動に際しては, 塞栓症の予防が問題となる. 慢性心房細動の除細動の適応ならびに塞栓の予防法については諸家の提言があるが, 一過性心房細動については症状の程度により, これらの提言にしたがえない場合もある. 今回我々は, 陳旧性心筋梗塞患者で発生した一過性心房細動のジソピラマイドによる薬物的除細動後にST上昇を呈した症例を経験した. 本例は無症候性ST上昇であったが, CPKなどの心筋逸脱酵素の上昇をともない, 冠動脈造影では冠攣縮は認めず, ジソピラマイド再静注でもST上昇は再現しなかった. 以上より, 一過性心房細動から洞調律に復帰する際に冠動脈塞栓を生じた可能性が高いと考えた. 薬物的除細動後に生ずる心筋梗塞類似の心電図変化についての報告はあるが, 伝導障害に起因するという報告が多い. ジソピラマイドによる報告がないことと, 本例では伝導障害よりも冠動脈塞栓の可能という報告が多い. ジソピラマイドによるリ報告がないことと, 本例では伝導障害よりも冠動脈塞栓の可能性が高いと考え九ので報告する. が高いと考えたので報告する.